URBAN MOBILITY DURING THE PANDEMIC IN YOGYAKARTA CITY - Imelda Irmawati Damanik; Yohanes Satyayoga Raniasta (Built Environment Studies, 2023)
The urban situation has changed during COVID-19 pandemic since 2020. The swift of mobility behavior happened in all over the city in the world. The WHO’s suggestion to maintain NPIs; the physical distancing is a push factor for people to reduce traveling and mobility. The slogan ‘stay at home’ became part of the new normal until nowadays, because publication of it was spread on all media to reach out the society. Yogyakarta City responds to the pandemic issue with the same strategy, minimizing mobility and travel. However, there is uniqueness in the practice on minimizing mobility and travel in 2020 and 2021. In 2020, the control of mobility and travel is based on community and in 2021 the control of mobility and travel is based on government policy. The security level of travel in 2020 is housing and urban kampung, and in 2021 is on the city level. The research is focused on the perception of respondent on minimizing travel and mobility between these two years. The data was analyzed using the Principle Component Analysis method. The quantitative result will be compared with observation, so it shows the important value to respond during uncertainty on travel and mobility issue. The study will give how local wisdom and public policy collaborate to produce urban resilience in Yogyakarta City.